A practical guide to monitoring for adverse drug reactions during antihypertensive drug therapy. - McDowell, SE; Thomas, S; Coleman, J; Aronson, J; Ferner, R (2013)
Monitoring of patients taking antihypertensive treatment can identify potential adverse drug reactions (ADRs). However, published guidelines give divergent or incomplete recommendations on monitoring for ADRs. Using a predetermined strategy, we undertook a systematic review to identify hypertension guidelines published from January 2001 to October 2011 with recommendations for monitoring for ADRs. We screened 88 abstracts and 187 web-based guidelines, and identified 19 published guidelines on monitoring the biochemical effects of antihypertensive drug therapy. We then produced a set of practical clinical guidelines, synthesized from those recommendations. Our recommendations are designed to provide efficient monitoring. They reduce the number of tests to a minimum consistent with safe practice and align monitoring schedules, so that creatinine, potassium and sodium concentrations are measured at the same times in all cases. The instructions for biochemical monitoring in current guidelines differ greatly, both in the extent of advice and in the detail provided. The current lack of consistent and workable instructions poses serious difficulties for practitioners. The recommendations distilled from this systematic review should help practitioners when they monitor therapy with antihypertensive drugs.